2001
DOI: 10.1038/sj.neo.7900185
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Screening of Genes Showing Altered Expression in Liver Metastases of Human Colorectal Cancers by cDNA Microarray

Abstract: In spite of intensive and increasingly successful attempts to determine the multiple steps involved in colorectal carcinogenesis, the mechanisms responsible for metastasis of colorectal tumors to the liver remain to be clarified. To identify genes that are candidates for involvement in the metastatic process, we analyzed genome-wide expression profiles of 10 primary colorectal cancers and their corresponding metastatic lesions by means of a cDNA microarray consisting of 9121 human genes. This analysis identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 10 publications
3
56
0
Order By: Relevance
“…Moreover, the studies have been mainly conducted on primary tumours and only very few data are available on metastases (Yanagawa et al, 2001;Koehler et al, 2004). This study first reports the gene expression profiling of liver metastases from colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the studies have been mainly conducted on primary tumours and only very few data are available on metastases (Yanagawa et al, 2001;Koehler et al, 2004). This study first reports the gene expression profiling of liver metastases from colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…normal mucosa, and also to evaluating the potential for metastases developing (Alon et al, 1999;Notterman et al, 2001;Yanagawa et al, 2001;Bertucci et al, 2004;Koehler et al, 2004;Li et al, 2004;Wang et al, 2004;Eschrich et al, 2005). Moreover, the studies have been mainly conducted on primary tumours and only very few data are available on metastases (Yanagawa et al, 2001;Koehler et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression analysis of colorectal biopsies using high density oligonucleotide microarrays could help detect such gene expression profiles that would establish the basis for new molecular diagnostic methods, and efforts have been made in this direction. In order to understand the gene expression background of CRC progression and metastasis development, many previous studies have primarily focused on the pair-wise comparisons of discriminative mRNA expression signatures between CRC and normal colorectal mucosa (NOR) samples, between CRA and NOR samples, as well as between the early and advanced stages of CRC (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Results from various studies have demonstrated that CRC and/or CRA have widespread genetic alterations compared to NOR (25)(26)(27).…”
Section: Identification Of An Intermediate Signature That Marks the Imentioning
confidence: 99%
“…In addition to the mutations to these important oncogenes, colon cancer initiation and progression are accompanied by changes in gene expression. Several microarray studies have been undertaken to more fully elucidate the changes in gene expression that occur during CRC initiation, progression and metastasis (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%